2008
DOI: 10.1128/jvi.00436-08
|View full text |Cite
|
Sign up to set email alerts
|

Llama-Derived Single-Chain Antibody Fragments Directed to Rotavirus VP6 Protein Possess Broad Neutralizing Activity In Vitro and Confer Protection against Diarrhea in Mice

Abstract: Group A rotavirus is one of the most common causes of severe diarrhea in human infants and newborn animals. Rotavirus virions are triple-layered particles. The outer capsid proteins VP4 and VP7 are highly variable and represent the major neutralizing antigens. The inner capsid protein VP6 is conserved among group A rotaviruses, is highly immunogenic, and is the target antigen of most immunodiagnosis tests. Llama-derived single-chain antibody fragments (VHH) are the smallest molecules with antigen-binding capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 52 publications
7
108
0
1
Order By: Relevance
“…This is supported by existing evidence that the phenotype of the outer layer VP4 can be altered by interactions with different VP7 proteins and of the marked impact of the protein-protein interactions among the constituent proteins of the RV inner, middle and outer layers (54). The neutralizing capacity associated with the recognition of crossreactive epitopes within VP6 of these antibodies may also relate to their small size, as bivalent VHH antibodies showed a much reduced neutralizing activity compared with the monovalent VHH, suggesting that these may have no or limited access to the exposed VP6 of an infectious triple-layered RV particle (50).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by existing evidence that the phenotype of the outer layer VP4 can be altered by interactions with different VP7 proteins and of the marked impact of the protein-protein interactions among the constituent proteins of the RV inner, middle and outer layers (54). The neutralizing capacity associated with the recognition of crossreactive epitopes within VP6 of these antibodies may also relate to their small size, as bivalent VHH antibodies showed a much reduced neutralizing activity compared with the monovalent VHH, suggesting that these may have no or limited access to the exposed VP6 of an infectious triple-layered RV particle (50).…”
Section: Figurementioning
confidence: 99%
“…Recently, the ARP1 llama-derived antibody that binds specifically to RV VP6 has been shown to bind to RV in ELISA and immune electron microscopy and to neutralize infection with a variety of RV genotypes in vitro using classical neutralization assays and in an in vivo mouse pup model, which suggests that these antibodies are likely to neutralize RV by immune exclusion (31,(50)(51)(52)(53). Although the mechanism by which the llama antibodies neutralize infection is not yet understood, it is possible that the VP6-specific VHH could block a conformational change in the outer layer proteins of the RV particle, VP7 and/or VP4, preventing attachment and/or entry of the virus particle, as previously suggested (31,50). This is supported by existing evidence that the phenotype of the outer layer VP4 can be altered by interactions with different VP7 proteins and of the marked impact of the protein-protein interactions among the constituent proteins of the RV inner, middle and outer layers (54).…”
Section: Figurementioning
confidence: 99%
“…The VHH domain can be easily cloned and expressed to high levels in bacteria and yeast (26,27). This notion, together with advantageous characteristics in terms of stability and solubility (20,64,81), has led to successful development of camelid VHH in a number of applications against a range of biological targets (2,13,14,19,21,57,58,69,83,84), including neutralization of rotavirus (28,60). We hypothesized that the small size of VHH in combination with their protruding CDR3 loops and their preference for cleft recognition may allow them to recognize conserved motifs on gp120 that are occluded from conventional antibodies.…”
mentioning
confidence: 99%
“…4h). VP6 possess broad neutralizing activity in vitro and confer protection against diarrhea in mice (Garaicoechea et al, 2008) and neonatal gnotobiotic piglets (Vega et al, 2013).…”
Section: Ifa Of Pv1 Antigen In Pv1 Infected Vero Cellsmentioning
confidence: 99%
“…For the last few years, studies have shown that VP6 could stimulate a protective immune response (Bugli et al, 2014;Li et al, 2014;Marashi et al, 2014;Pastor et al, 2014;Shoja et al, 2015) and a short fragment of VP6 could provide significant reduction in virus infectivity in vitro (El-Senousy et al, 2013). Previous experiments demonstrated that anti-VP6 llama-derived single-chain antibody fragments (VHH) had neutralizing activity against VP6 in vitro (Garaicoechea et al, 2008). Using RV VP6 as a vector (VP6F), the chimeric proteins carrying epitopes derived from the VP4 of RV were constructed and demonstrated that these chimeric proteins had good antigenic reactivity and immunogenicity (Teng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%